Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1109/jphot.2020.3041731
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Mach-Zehnder Interferometer Liquid Refractive Index Sensor Based on Conventional Polymer Strip Waveguide

Abstract: We propose and demonstrate a cost-effective liquid refractive index (RI) sensor in polymer materials by employing a Mach-Zehnder interferometer (MZI) formed with the conventional strip waveguide. The proposed sensor can attain high sensitivity by choosing a suitable reference arm length to reduce optical path difference (OPD) between the two arms of the employed MZI. Our fabricated devices, which have the same sensing arm length of 7900 µm but different reference arm lengths of 7900.0, 7942.5, 7950.9, 7962.2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Considering that the loss of the SR is larger than that of the RR, and the results of previous work [5], the power splitting ratio in YJ 2 is designed to be ∼2:1 in this work to make more light power into the SR to balance the loss, that is,…”
Section: Table I Geometric Parameters Of Our Designed Rr and Sr (Unit...mentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that the loss of the SR is larger than that of the RR, and the results of previous work [5], the power splitting ratio in YJ 2 is designed to be ∼2:1 in this work to make more light power into the SR to balance the loss, that is,…”
Section: Table I Geometric Parameters Of Our Designed Rr and Sr (Unit...mentioning
confidence: 99%
“…most attractive device configurations due to its small size and strong light-analyte interaction achieved by the resonance of light wave in ring waveguide, making it the best choice for building compact and high-sensitivity sensors [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They can also be applied in high-temperature environments and have the capability to be free of electromagnetic interference, which complements the vulnerability to electromagnetic interference and long sensing time of traditional electrical sensors [4,5]. Refractive index sensors are a significant type of liquid optical waveguide sensors that allow for highly sensitive detection and measurement of refractive index changes in the surrounding medium [6]. Optical liquid sensors convert the change in refractive index of an analyte into an optical signal via the interaction between light and the analyte, which achieves sensitive, real-time detection of the analyte [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of polymer sensing, strip waveguides and slot waveguides on substrates are widely employed. In 2020, Xiao Xia Ma et al proposed and demonstrated a cost-effective liquid refractive index (RI) sensor in polymer materials by employing a Mach–Zehnder interferometer (MZI) formed with the strip waveguide [ 19 ]. Kaixin Chen et al proposed a polymer horizontal slot waveguide as a light-analyte interactive region to implement a low-cost and highly sensitive liquid refractive index sensor [ 20 ].…”
Section: Introductionmentioning
confidence: 99%